Estimating medical costs of work-related diseases in the basque country (2008) / Costi medici delle malattie attribuibili al lavoro nei Paesi Baschi (2008) - García Gómez, Montserrat; Castañeda López, Rosario; López Menduiña, Patricia; Urbanos Garrido, Rosa; Markowitz, Steven (La Medicina del Lavoro, 2013)
Objectives: To estimate the medical costs of work-attributable diseases (WAD) treated by the public health caresystem for one of the Spanish Autonomous Communities, the Basque Country, in 2008. Methods: We calculatedthe burden of disease attributable to work for each category of diseases according to ICD-9-CM by using estimatesof attributable fractions. Hospital and specialized outpatient care cost data were derived from the Spanish NationalHealth System analytical accountability system. Secondary sources of information were used to estimate primaryhealth care and drug prescriptions. Results: Direct costs of work-attributable diseases borne by the Basque RegionalHealth Service totalled 106 million Euros in 2008, representing 3.3% of Basque public expenditures on health and0.16% of Basque GDP in 2008. Specialized care, including hospitalizations, absorbed the highest proportion ofcosts (52%), followed by drug prescriptions and primary health care (27% and 21%, respectively). Diseases of themusculoskeletal system and connective tissues accounted for 47.3% of total costs, followed by cardiovascular diseases(19.6%) and cancer (15%). Conclusions: Occupational diseases and accidents are costly in the Basque Region ofSpain, generating a severe deviation of public expenditures and overburdening of the Public Health System becausethey should really be the responsibility of the Social Security System. Proper identification and assignment of costs ofwork-related diseases would result in significant savings for the National Health System (Spanish and European),would provide an incentive for the prevention of these avoidable causes of illness and thus contribute to the sustainabilityof social systems.Costi medici delle malattie attribuibili al lavoro nei Paesi Baschi (2008)Obiettivi: Stimare i costi sanitaridiretti delle malattie attribuibili al lavoro nei Paesi Baschi nel 2008.Metodi: Abbiamo calcolato le malattie attribuibilial lavoro per ciascuna categoria di malattie secondo ICD-9-CM e le frazioni attribuibili al lavoro nella letteratura scientifica. I dati primari derivanti dal sistema di contabilità analitica del Servizio Sanitario Nazionalespagnolo sono stati usati per calcolare i costi relativi ai ricoveri e alle prestazioni ospedaliere. Fonti secondarie diinformazione sono state utilizzate per stimare il costo dell’assistenza sanitaria primaria e le prescrizioni farmaceutiche.Risultati: I costi sanitari diretti delle malattie lavoro-correlate nel Servizio Sanitario Basco sono stati 106milioni di euro nel 2008. Essi rappresentavano il 3,3% della spesa pubblica basca in materia di sanità e lo 0,16%del PIL nel 2008. L’assistenza specializzata, tra cui i ricoveri, assorbe la più alta percentuale dei costi (52%), seguitadalle prescrizioni di farmaci e dell’assistenza sanitaria di base (27% e 21%, rispettivamente). Le malattie delsistema muscolo-scheletrico e dei tessuti connettivi rappresentano il 47,3% dei costi totali, seguite dalle malattie cardiovascolari(19,6%) e dai tumori (15%). Conclusioni: Le malattie lavoro-correlate nei Paesi Baschi sono costosee rappresentano un importante aggravio per la spesa pubblica e per il Servizio Sanitario Nazionale, anche perchéquesta spesa dovrebbe essere più correttamente attribuita al Sistema di Previdenza Sociale. La corretta identificazionee assegnazione dei costi delle malattie lavoro-correlate può tradursi in un notevole risparmio per il SistemaSanitario, e può costituire un incentivo per la prevenzione delle malattie lavoro-correlate e perciò una maggiore sostenibilitàdei sistemi sociali.